SOCIAL DISTANCE ENCOURAGER AND MOTIVATION SYSTEM - Bhavya Sekhani; Manan Mahajan (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper details the development of a wearable device that would encourage and motivate people to maintain social distancing, thus also ensuring the safety and health of individuals. React Native, Redux and, Async storage has been used for the front-end development whereas NodeJS, ExpressJS and, MySQL have been used for the back-end. The distance is monitored with a smartphone’s in-built geo-location sensor, warning the user to maintain a distance of six feet. To obtain higher accuracy, ultrasonic sensors are used in conjunction with the mobile application. The band is tethered with the mobile to alert the user once the six-feet norm is violated.